2013
DOI: 10.1111/josh.12119
|View full text |Cite
|
Sign up to set email alerts
|

Learning From Successful School‐Based Vaccination Clinics During 2009 pH1N1

Abstract: Utilizing rigorous methodology, we defined and learned lessons from successful LHDs when conducting school-based vaccination clinics, which can be applied to future school-based vaccination campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 13 publications
(16 reference statements)
1
30
0
Order By: Relevance
“…Several US studies of H1N1 vaccination provided examples of the direct impact that the federal government’s emergency-driven response to pandemic influenza had on the delivery of school-based programmes and public attitudes towards this [14, 28, 30, 32]. For example, one paper explored how the declaration of a public health emergency, and the associated federal legislation that was enacted, gave some schools enough assurance for important programme enablers to be adopted such as school nurses acting as vaccinators [27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several US studies of H1N1 vaccination provided examples of the direct impact that the federal government’s emergency-driven response to pandemic influenza had on the delivery of school-based programmes and public attitudes towards this [14, 28, 30, 32]. For example, one paper explored how the declaration of a public health emergency, and the associated federal legislation that was enacted, gave some schools enough assurance for important programme enablers to be adopted such as school nurses acting as vaccinators [27].…”
Section: Resultsmentioning
confidence: 99%
“…However, these were descriptive or qualitative studies in which few associations were directly made with success. In 2009 pre-existing partnerships between public health departments and education agencies appeared to allow a rapid response to be mobilised for H1N1 vaccination [27, 30]. Also in the US, school managers and school nurses reported that “good” relationships between the local health department and local school management were necessary for programmes to be effective [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For other vaccines, some countries have successfully implemented national or regional immunization campaigns in the face of an epidemic. [31][32][33][34][35][36] While awaiting development of new vaccines that will provide long-lasting protection against pertussis, we should consider alternate Tdap immunization strategies for adolescents. …”
Section: Discussionmentioning
confidence: 99%